1975
DOI: 10.1002/1097-0142(197503)35:3<714::aid-cncr2820350326>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of survival and recurrence vs. patient and doctor delay in treatment of breast cancer

Abstract: Two hundred thirty-seven patients with cancer of the breast treated with radical mastectomy were reviewed. Coefficients of correlation between patient's and doctor's delay vs. survival were not significant at p smaller than 0.05. No significant relationship between delay and time of recurrence was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
42
0
2

Year Published

1975
1975
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 19 publications
10
42
0
2
Order By: Relevance
“…This is in agreement with findings from pertinent studies published during the last decade (Coates et al, 1992;Afzelius et al, 1994;Burgess et al, 1998) and is further evidence of a favourable trend towards shorter delay during the last two decades when compared with earlier studies (Cameron and Hinton, 1968;Dennis et al, 1975;Fisher et al, 1977;Elwood and Moorehead, 1980;MacArthur and Smith, 1981;Dohrmann et al, 1982;Vernon et al, 1985;Neale et al, 1986). This trend might be attributable to an increasing health awareness among women due to extensive information campaigns which address breast cancer warning signs in many developed countries.…”
Section: Discussionsupporting
confidence: 90%
“…This is in agreement with findings from pertinent studies published during the last decade (Coates et al, 1992;Afzelius et al, 1994;Burgess et al, 1998) and is further evidence of a favourable trend towards shorter delay during the last two decades when compared with earlier studies (Cameron and Hinton, 1968;Dennis et al, 1975;Fisher et al, 1977;Elwood and Moorehead, 1980;MacArthur and Smith, 1981;Dohrmann et al, 1982;Vernon et al, 1985;Neale et al, 1986). This trend might be attributable to an increasing health awareness among women due to extensive information campaigns which address breast cancer warning signs in many developed countries.…”
Section: Discussionsupporting
confidence: 90%
“…This may also help to explain some of the apparently contradictory findings in the literature. Reports published since 1970 that have shown no significant relationship between delay and survival have generally been confined to patients with early stage (operable) disease (Alderson et al, 1971;Dennis et al, 1975;Wallgren et al, 1976;Fisher et al, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported in the past 30 years have indicated that survival is worse among women with longer duration of symptoms (Sheridan et al, 1971;Wilkinson et al, 1979;Elwood and Moorehead, 1980;Feldman et al, 1983;Charlson, 1985;Vernon et al, 1985;Huguley et al, 1988;Machiavelli et al, 1989;Rossi et al, 1990;Neave et al, 1990;Rabinovich et al, 1993;Afzelius et al, 1994;Raabe et al, 1996). Other studies, however, have not shown that survival is affected by duration of symptoms (Dennis et al, 1975;Fisher et al, 1977;Hainsworth et al, 1993) These apparently conflicting results may possibly be explained by differences in sample characteristics (e.g. inclusion of patients with all stages of breast cancer or restriction of the sample to patients with operable disease only), by differences in the delay interval studied (e.g.…”
mentioning
confidence: 99%
“…[11][12][13][14][15][16][17] Second, after diagnosis, minority women experience delays in the initiation and completion of treatment. [18][19][20] Third, there are differences in the type of treatment received by African American and Hispanic women. [21][22][23] Fourth, African American women are more likely to receive fewer cycles of the expected treatment compared with white women.…”
mentioning
confidence: 99%